2018
DOI: 10.2298/tsci151110147s
|View full text |Cite
|
Sign up to set email alerts
|

Impact of electrical and magnetic field on cooling process of liquid metal duct magnetohydrodynamic flow

Abstract: Cooling period of liquid metal while flowing under imposed magnetic and electrical field was studied for laminar steady flow condition. Computational analyses were done by ANSYS Fluent software MHD module. For applied each constant value of magnetic field induction (B = 0 T, B = 0.05 T, B = 1 T), the electrical field intensity was applied positively as E + (1e-4, 1e-5) V/m and negatively as E − (-1e-4,-1e-5) V/m. Increase of the E+ field intensity decreased the local temperature (increased cooling rate) but al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…ANSYS is an engineering software program to solve the problem of strength, toughness, elasticity, deformations, heat transfer, fluid flow, electromagnetism, etc (Belhocine & Bouchetara, 2012;Çayıroğlu et al, 2017;Recebli et al, 2016;Selimli et al, 2015;Selimli & Recebli, 2018). Most users prefer to the ANSYS Workbench system for simulations.…”
Section: Simulation Of Finite Element Methodsmentioning
confidence: 99%
“…ANSYS is an engineering software program to solve the problem of strength, toughness, elasticity, deformations, heat transfer, fluid flow, electromagnetism, etc (Belhocine & Bouchetara, 2012;Çayıroğlu et al, 2017;Recebli et al, 2016;Selimli et al, 2015;Selimli & Recebli, 2018). Most users prefer to the ANSYS Workbench system for simulations.…”
Section: Simulation Of Finite Element Methodsmentioning
confidence: 99%
“…ANSYS Fluent software MHD module was used in the calculations. As a result, it has been observed that depending on the direction of the magnetic or electric field applied on a liquid fluid, heat transfer can be increased or weakened [12]. In order to increase the amount of heat transfer, there are options to increase the heat transfer coefficient, increase the temperature difference and increase the area based on the Fouirer equation.…”
Section: Nanofluidtechnologiesmentioning
confidence: 99%
“…The minimum relative difference of the average temperature and heat flux value are 0.037% and 0.515% between the set of grids with 1,20,258 and 1,38,702 nodes. So, the set of grids with 1,38,702 nodes to 1,20,258 nodes are selected with the objective to minimize the computational time (Kelly et al, 2015; Selimli and Recebli, 2018). The adiabatic condition to the side walls of the substrate is applied by assuming zero heat flux values to the wall.…”
Section: Experimental and Numerical Analysismentioning
confidence: 99%